Economic Growth and Poverty Reduction in Colombia - Adriana Rocío Cardozo Silva (Peter Lang International Academic Publishers, 2010)
This book analyses the distributional effects of economic growth on different dimensions of poverty in Colombia. It provides a microeconomic perspective on how economic growth affected poverty and inequality at the household level, as well as a macroeconomic perspective on the effects of growth on regional living standards. The study incorporates recent discussions on multidimensional analysis of well-being and goes beyond traditional income based measures, thereby contributing to the ongoing research on how to measure pro-poor growth and on the importance of incorporating different dimensions of well-being in convergence analysis.
Keywords: 330